Принятие решений в парламенте Украины, или Доктор Джекилл и мистер Хайд украинского парламентаризма - Зоткин, А. (Социология: теория, методы, маркетинг, 2007)
Comparative research concerning temporal aspects of the decisions that have been made on economic and social issues by the Verkhovna Rada's deputy corps is aimed at elucidating some implicit mechanisms of the lingering political crisis in our country.Collation of data covering the years 2002—2004, 2005, and 2006—2007 allows observing instability of positions taken by different groups of the Ukrainian political elite according to whether they happened to be — in power or in opposition. So, there are reasonable grounds to suppose that now the Ukrainian ruling forces are tending away from their monocentric structure and moving towards a polyarchical one. In the course of time this circumstance may contribute to democratization of Ukrainian society.